Krajinski kodi v slovenski umetnostni zgodovini - Zgonik, Nadja (Monitor ISH, 2006)
The early 1920s saw the emergence of a new art historical methodology, the so-called art geography. Art geography emphasised the influence of spatial circumstances on a certain type of cultural production, examining geomorphological features and climate conditions as well as the role of social circumstances, national identity in particular. After reaching its peak in the 1930s, this art historical method was discredited and largely forgotten. It may be claimed, however, that the European nations who played a minor role in the history of art developed it at the time into a methodology which still proves useful in studying the identities of marginal cultural and social groups and areas.
Keywords: art history; umetnostna zgodovina; umetnostna geografija; nacionalna identiteta; regionalna identiteta; prostorska identiteta; krajinsko slikarstvo; geozgodovina umetnosti